Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting

Bright dual-phase organic luminescence from zero-dimensional lead halide hybrids via sensitized thermally activated delayed fluorescence for multifunctional applications - Kumar Das, Deep; Sarma, Dhritismita; Kumar, M. Praveen; Khan, Akram Aadil; Madhusoodhananan, Mahesh; Kudlu, Ashwath; Ajithkumar, Thalasseril Govindankuttykaimal; Pujala, Ravi Kumar; Mahata, Arup; Kundu, Janardan (Chemistry of Materials, 2026)
Metal halide hybrids have long celebrated their halometallate moieties as the luminescent center, leaving organic cations behind. Although the thermally activated delayed fluorescence (TADF) strategy has enabled efficient solid-state organic emitters, the complex molecular design required for TADF emitters has limited their facile integration into metal halide hybrid architectures. Here, we demonstrate a versatile strategy wherein a nonemissive organic moiety (benzyltributylammonium) is incorporated into a zero-dimensional disphenoidal Pb-halide hybrid, [(C19H34N)2PbCl4], resulting in efficient TADF-based dual-phase organic emission sensitized by halometallate units in the solid state (crystalline; amorphous). These materials exhibit strong PLQY (similar to 85%) and tunable organic luminescence (blue emission in crystalline phase; cyan emission in amorphous phase) modulated by the packing extent of organic moiety. [PbX4]2- units act as absorptive centers that sensitize organic cations showing TADF-based strong emission. Ground and excited state density functional theory calculations reveal the unique origin of sensitized TADF organic luminescence. Rheological measurements characterize relaxation dynamics of glass <-> supercooled liquid transitions, establishing correlations between molecular packing, phase, and emission characteristics. This first demonstration of dual-phase, sensitized TADF-based organic luminescence in lead halide hybrids establishes a new design paradigm that bridges molecular and solid-state photophysics, opening avenues for multifunctional applications in LEDs, optical thermometry, and security technologies.